BclI Polymorphisms of NR3C1 Gene and sST2 Levels Among Asthmatic Patients Under Steroid Treatment - Ahmed Salman Khaleel; Ekhlas Saddam Falih; Hind Jaber Hassoon (Diyala Journal of Medicine, 2025)
Background: Asthma is an allergic disorder affecting the lower respiratory tract and causing lung problems such as wheezing, coughing, and a sensation of chest constriction. Environmental, immunological, and genetic factors play a crucial role in the development of hyper-responsivity and bronchial obstruction. Objectives: This study aimed to estimate the serum concentrations of soluble Growth Stimulating Expression Gene 2 Protein (sST2) and to assess and analyze the Single Nucleotide Polymorphism (SNP) of the NR3C1 gene (BclI rs41423247) in asthmatic patients under treatment and healthy controls. Patients and Methods: This study included 80 asthmatic patients and 40 controls. sST2 was quantified using an enzyme-linked immunosorbent assay (ELISA). DNA was extracted from blood samples, followed by PCR amplification using a thermocycler with a newly designed, gene-specific primer pair targeting the NR3C1 gene. The Sanger sequencing technique detected the BclI rs41423247 SNP. Results: The results show a highly significant difference in sST2 levels between asthma patients and controls (55.43±15.81 vs. 38.04±5.215, respectively), with the highest levels observed in severe asthma patients (60.72±21.38). According to the treatment type used, the highest sST2 levels were seen in the G2 group, while the lowest levels were observed in the G1 group. The GC genotype of the BclI rs41423247 SNP is more common in patients (31.25%) than in controls (10%) (P value = 0.0103, χ2 = 6.571, and OR= 4.091). Conclusion: The current study concluded that individuals with the BclI rs41423247 polymorphism in the NR3C1 gene can develop asthma compared to individuals without this defect. Furthermore, the GC genotype of the BclI rs41423247 can affect the effectiveness of the steroid used, directly or indirectly, by its role in glucocorticoid receptor expression. This leads to a persistent inflammatory process associated with increased serum sST2 levels. Keywords: Asthma, BclI, glucocorticoid receptor, Single nucleotide polymorphism, Soluble growth stimulating expression gene 2 protein.